2016
DOI: 10.1002/ppul.23639
|View full text |Cite
|
Sign up to set email alerts
|

How do we recognize the child with OSAS?

Abstract: Obstructive sleep-disordered breathing includes a spectrum of clinical entities with variable severity ranging from primary snoring to obstructive sleep apnea syndrome (OSAS). The clinical suspicion for OSAS is most often raised by parental report of specific symptoms and/or abnormalities identified by the physical examination which predispose to upper airway obstruction (e.g., adenotonsillar hypertrophy, obesity, craniofacial abnormalities, neuromuscular disorders). Symptoms and signs of OSAS are classified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 125 publications
0
42
0
5
Order By: Relevance
“…The present state‐of‐the‐art review is the second in a series of three articles discussing recent advances in the diagnosis and management of OSAS. The first article of the series focused on the recognition of the child with OSAS (“How do we recognize the child with OSAS?”) . The aim of the present article is to summarize findings of key studies based on which the clinician will (i) identify children with OSAS who may get the most benefit from treatment interventions; (ii) recognize clinical parameters that are associated with increased likelihood of spontaneous improvement or resolution of OSAS without treatment interventions; (iii) give guidance to parents whose children have primary snoring, that is, they have no recognizable apneas, hypopneas, or gas exchange abnormalities during sleep.…”
Section: Introductionmentioning
confidence: 99%
“…The present state‐of‐the‐art review is the second in a series of three articles discussing recent advances in the diagnosis and management of OSAS. The first article of the series focused on the recognition of the child with OSAS (“How do we recognize the child with OSAS?”) . The aim of the present article is to summarize findings of key studies based on which the clinician will (i) identify children with OSAS who may get the most benefit from treatment interventions; (ii) recognize clinical parameters that are associated with increased likelihood of spontaneous improvement or resolution of OSAS without treatment interventions; (iii) give guidance to parents whose children have primary snoring, that is, they have no recognizable apneas, hypopneas, or gas exchange abnormalities during sleep.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence rate of OSAHS in children is 1–3%, presenting a rising trend and no difference between genders (11 13). This study confirmed that there was no statistical difference in terms of age and gender proportion for pediatric patients with different disease severities.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its shortcomings, oximetry is a simple, economical, and readily available tool which can be easily performed at home. Although a negative oximetry study cannot rule out OSA, the perioperative risk of respiratory complications is low for a healthy child with a history of snoring who has had negative or inconclusive oximetry score . As such, overnight oximetry should be considered a practical tool to identify at‐risk children of postoperative complications, although the aforementioned limitations need to be acknowledged.…”
Section: Oximetrymentioning
confidence: 99%
“…Despite this poor correlation between severity of sleep‐disordered breathing as measured by a PSG and the clinical signs and symptom appears being well recognized, it remains essential that every evaluation of a child with suspected OSA begins with a thorough history including consideration of parental concerns of a child's sleep breathing. Indeed, a snoring history should be a component of all routine health assessments of any child.…”
Section: Clinical Measures Of Osamentioning
confidence: 99%